IMPLEMENTATION OF SCIENCE PROCESS SKILLS DURING THE COVID-19 PANDEMIC - Adinda Arlin Husniyyah; Erman Erman (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
This study aims to identified the science process skills implementations and the barriers during online learning at State Junior High School 1 Sidoarjo. This study used case studies at State Junior High School 1 Sidoarjo with the participants of this study were 3 science teachers and 15 students 7th grade. Data collection techniques used observation, documentation, and interviews then analyzed descriptively to got more detailed information about SPS’ implementations. The study’s instruments were teacher and student questionnaires. The results showed that some indicators of science process skills decreased from offline to online learning. The most significant decreased on formulating hypotheses, experimenting, identifying variables, and interpreting data. Only one of three teachers has capability to implement it. Meanwhile, SPS’ indicators that has been implemented optimally by all teachers were observing, measuring, inferring, and communicating. The barriers of the SPS’ implementations in online learning were time, student condition, and teachers SPS’ ability. The suggestion for the further research to giving a solution for science teachers to manage SPS’ activities and make some training to improve teachers SPS’ ability, from the SPS’ theory and the skills to integrate SPS activities on student worksheet.